PERCEPTIONS OF TRANSFORMATIONAL LEADERSHIP OF SCHOOL PRINCIPLES AND WORK ENGAGEMENT TO PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT - Marcy Sulistyo Putri (Universitas Airlangga, 2023)
This study aims to analyze and examine the effect of leadership perception.commitment organizational to employees at Surabaya Grammar School. This study uses a quantitative approach with an explanatory method and a sampling technique that is total sampling with a total of 90 respondents. The data analysis technique used is the path analysis. The results of this study conclude, among others: 1.) Principal's perception of transformational leadership has a positive and significant effect on organizational commitment; 2.) Job involvement has a positive and significant effect on organizational commitment; 3.) Principal's perception of transformational leadership has a positive and significant effect on performance; 4.) Work involvement has a positive and significant effect on performance; 5.) Organizational commitment has a positive and significant effect on performance; 6.) Principal's perception of transformational leadership influences performance through positive and significant organizational commitment; 7.) Work involvement has an effect on performance through positive and significant organizational commitment.